Quantile Analysis of Oil Price Shocks and Stock Market Performance: A European Perspective - Audi, Marc; Poulin, Marc; Ahmad, Khalil; Ali, Amjad (International Journal of Energy Economics and Policy, 2025)
This study investigates the interplay between oil price variations and stock market performance in Europe over the period 1991–2023. By analysing Europe as a cohesive economic entity, the research provides a unified view of how trends in energy markets and broader macroeconomic factors affect equity outcomes. The methodology combines ordinary least squares and quantile regression to robustly capture average impacts and variations across different segments of stock returns. Findings reveal that rising oil prices typically exert downward pressure on European equities by increasing production costs in petroleum-reliant industries. However, abrupt oil price shifts have nuanced effects: some segments exhibit heightened sensitivity, while others remain resilient, suggesting that adaptive industries may fare better than energy-intensive ones. Additionally, strong economic growth often intensifies fears of inflation, interest rate hikes, and market overheating, creating a negative association with stock performance. Inflation challenges equities, with higher-performing stocks especially vulnerable to price increases. The shift toward renewable energy appears to have short-term adverse effects, largely due to capital redistribution and transitional hurdles affecting traditional energy sectors. These results offer guidance for stakeholders. It underscores the need to align energy strategies with equity markets. Policymakers can enhance market resilience by addressing oil price volatility through transparency and risk mitigation, and by clearly communicating monetary policies to reduce inflation-induced uncertainty. While accelerating renewable adoption is vital for sustainability, careful management is needed to minimize disruptions to established sectors. Firms should hedge against energy price risks and invest in cleaner technologies to remain competitive in a changing landscape.